THE RELATIONSHIP OF PHILOSOPHY, SOCIOLOGY AND PEDAGOGY IN THE WORK OF GEORG SIMMEL - Danner, Stefan (Socialinė teorija, empirija, politika ir praktika, 2009)
"Relationship" is an important term in the work of Georg Simmel (1858 - 1918). Simmel used this or familiar term to describe completely different processes and structures. In this essay attempts will be made to apply the concept of relationship to the work of Simmel itself. The aim is to demonstrate particularly interesting links between Simmel's philosophy, sociology and pedagogy. The intention of the essay is not to give extensive interpretations of Simmel’s philosophy, sociology and pedagogy, but to show in general terms that at least four Simmel's ideas create a strong relationship between his philosophy, sociology and pedagogy. The results of analysis demonstrate that there is relationship between Simmel’s philosophy, sociology and pedagogy and it is possible to find many developments, transformations and sometimes surprising variations of the theme.
Keywords: Simmel; Relationship; Philosophy; Sociology; Pedagogy